2020
DOI: 10.3389/fbioe.2020.00961
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Bio-Based Washing Agent and Its Application for Removal of Petroleum Hydrocarbons From Drill Cuttings Before Bioremediation

Abstract: Drill cuttings from petroleum exploration and production sites can cause diverse environmental problems. Total petroleum hydrocarbons (TPHs) are a major pollutant from the use of polyolefin-based mud. As an alternative to incineration, this study investigated the application of surfactant-enhanced washing technology prior to bioremediation. The washing step was necessary because the initial TPH concentrations were quite high at approximately 15% (w/w). Washing agents were formulated by varying the concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Buathip (2018) reported that the CMC of LS3 obtained from the adsorption on the VBE‐solid surface at a solution pH of 7.0 ± 0.5 at room temperature was approximately 3 vol.%. These results are consistent with those of Arpornpong et al (2020), who found that the greater total petroleum hydrocarbon removal was observed as the biosurfactant concentration increased beyond its CMC value.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Buathip (2018) reported that the CMC of LS3 obtained from the adsorption on the VBE‐solid surface at a solution pH of 7.0 ± 0.5 at room temperature was approximately 3 vol.%. These results are consistent with those of Arpornpong et al (2020), who found that the greater total petroleum hydrocarbon removal was observed as the biosurfactant concentration increased beyond its CMC value.…”
Section: Resultssupporting
confidence: 93%
“…In contrast, negative HLD values (HLD < 0) are obtained for hydrophilic surfactants that produce a Winsor type I microemulsion. For soil washing applications, the washing solution is formulated at HLD = 0 because a Winsor type III microemulsion gives the lowest interfacial tension (IFT) between the washing solution and the oil, resulting in high oil removal efficiency (Arpornpong et al, 2018, 2020; Naksuk et al, 2009; Tongcumpou et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental results indicated that the oil phase recovery rate was more than 85%, and the total petroleum hydrocarbon content (TPH) of waste residues was less than 2% after the cleaning. In addition, some scholars used biobased surface cleaning agents instead of chemical cleaning agents to remove hydrocarbons in drilling cuttings before microbiological treatment, and the content of hydrocarbons in biologically treated drilling cuttings decreased to less than 1% [54,55]. Compared with single biodegradation or chemical cleaning, the combination of chemical cleaning and biodegradation is more efficient for treating OBDC.…”
Section: Microbiological Degradationmentioning
confidence: 99%
“…Helmy et al [16] successfully applied a rhamnolipid biosurfactant in the formulation of a washing biodetergent, whose stain removal efficiency was close to that of a standard detergent, thus showing potential as a promising substitute for synthetic surfactants. Arpornpong et al [17] prepared cleaning agents at variable salinity values by changing the concentrations of a lipopeptidic biosurfactant, the natural surfactant Dehydol LS7TH (D) and butanol as a hydrophobic binder. The best formulation led to an oil-in-water (O/W) microemulsion with polyolefin containing no more than 20% (v/v) foam and 2% (v/v) D. Thanks to the synergism of anionic lipopeptides with nonionic D, the preparation was able to remove, in a jar test, > 90% of total petroleum hydrocarbons adsorbed on drill cuttings and fragments.…”
Section: Introductionmentioning
confidence: 99%